Cutting Up Matthew Bourne's Edward Scissorshands - Mackrell, Judith (Dance Books Ltd., Alton,Hampshire (UK), 2006)
Matthew Bourne's Edward Scissorshands PALABRAS CLAVE: Matthew Bourne, Tim Burton, Edward Scissorshands.